On the question of transformation of forms and methods of military actions in the conditions of hybrid wars - Semenenko, Oleh; Deineha, Oleksandr; Voronchenko, Ihor; Borysiuk, Serhii; Mytchenko, Serhii; Taran, Olha (Social Development and Security, 2021)
Today, the concept of hybrid warfare refers to the latest, non-standard methods of warfare, a general consensus on its final definition has not yet been reached. Now it is impossible to draw up plans for the use of our own defense forces in accordance with possible scenarios of crisis situations of a military nature with certain forms and methods of conducting military operations and the sequence of their use without taking into account the influence of the factor of possible hybridization of military operations in any scenario of possible situations of a military nature. The article is devoted to highlighting different views on the concept of hybrid warfare, determining its main components and features, as well as determining the features of the influence of the hybridization factor on the choice of forms and methods of conducting military operations under various scenarios for the development of military crisis situations. In the article, the authors present the results of assessing the influence of various factors on the forms and methods of conducting military operations, determine the role of the factor of hybridization of military operations during their impact, form views on a possible solution to the problems of substantiating the choice of a rational sequence of application of forms and methods in solving the problems of a particular scenario of different crisis situations of a military nature. The authors propose the development of a scientific and methodological apparatus for adapting the forms and methods of conducting military operations in the conditions of their hybridization, one of the main elements of which should be a methodology for substantiating the choice of a rational sequence of forms and methods of using the defense forces of Ukraine in accordance with the conditions for the development of crisis situations of a military nature and possible scenarios their decisions.